2003
DOI: 10.1111/j.1744-7348.2003.tb00303.x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of a mutation that alters the floral symmetry in sunflower

Abstract: The indeterminate inflorescence of sunflower (Helianthus annuus) is heterogamous with zygomorphic ray flowers in the outer whorl of the head and actinomorphic disc flowers arrayed in arcs radiating from the centre of the head. The Chrysanthemoides (Chry) mutant is characterised by a change of the radially symmetric corolla of tubular disc flowers into a monosymmetric ligulate-like corolla. Zygomorphy is pronounced in the disc flowers placed on the peripheral whorls of inflorescences, while the monosymmetry is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 24 publications
(41 reference statements)
0
36
0
Order By: Relevance
“…By contrast, Antirrhinum and Linaria mutations affecting floral symmetry showed no drastic effects on carpel development (Carpenter and Coen 1990;Luo et al 1996Luo et al , 1999Almeida et al 1997;Cubas et al 1999;Galego and Almeida 2002). In sunflower, the Chry mutation has been suggested to affect stamen development (Jaranowski et al 1977;Fambrini et al 2003a), as well as ovule formation in disk flowers of homozygous mutants (Fambrini et al 2003a). …”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…By contrast, Antirrhinum and Linaria mutations affecting floral symmetry showed no drastic effects on carpel development (Carpenter and Coen 1990;Luo et al 1996Luo et al , 1999Almeida et al 1997;Cubas et al 1999;Galego and Almeida 2002). In sunflower, the Chry mutation has been suggested to affect stamen development (Jaranowski et al 1977;Fambrini et al 2003a), as well as ovule formation in disk flowers of homozygous mutants (Fambrini et al 2003a). …”
Section: Introductionmentioning
confidence: 84%
“…A preliminary characterization (Fambrini et al 2003a) of homozygous Chry/Chry plants revealed a shift from the polysymmetric corolla typical of disk flowers to a monosymmetric ray-like corolla (Fig. 1e).…”
Section: Cross Generationmentioning
confidence: 96%
See 1 more Smart Citation
“…The number of ray (ligulate) flowers of the outer whorl of the head in H. annuus is genetically determined (Luczkiewicz 1975) and can be considered to be a specific qualitative trait characterizing putative hybrids (Fambrini et al 2003). Therefore, to determine the effect of the intergeneric cross, we evaluated the new sunflower lines by their morphological floral characteristics (Table 1).…”
Section: Postharvestmentioning
confidence: 99%
“…Total variant plants found per year ranged from 28 (2007) to 103 (2008), the largest number following the most drastic disturbance. The site may have received toxic waste disposal causing a mutation that resulted in persisting aberrations not unlike some reported for other Asteraceae (Fambrini et al 2003).…”
mentioning
confidence: 99%